Extending pedagogies for language learning - Fatimah Hashim (Penerbit Universiti Malaya, 2015)
This book provides practical ideas for those working in the field of language teaching besides giving the necessary theoretical background. It can also work as a training reference. The book is aimed at teachers, teacher educators, and workshop facilitators involved both in pre-service and in-service education of teachers of second and foreign languages. Pedagogical aids such as diagrams and sample exercises round out this practical and useful text.